The Usborne First Cookbook - Angela Wilkes; Stephen Cartwright (Usborne Publication, 1987)
This book takes you step-by-step through recipes for all sorts of delicious things, fun to make and good to eat. They all teach you the basics that every good cook needs to know. It includes: hot things, sweet things, and party things.
Keywords: Cooking Book -- Cooking Book